2011
DOI: 10.5194/amt-4-245-2011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and intercomparison of aerosol absorption photometers: result of two intercomparison workshops

Abstract: Abstract. Absorption photometers for real time application have been available since the 1980s, but the use of filterbased instruments to derive information on aerosol properties (absorption coefficient and black carbon, BC) is still a matter of debate. Several workshops have been conducted to investigate the performance of individual instruments over the intervening years. Two workshops with large sets of aerosol absorption photometers were conducted in 2005 and 2007. The data from these instruments were cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
307
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 312 publications
(329 citation statements)
references
References 49 publications
16
307
3
3
Order By: Relevance
“…For the TFE-coated glass filter we obtained C ≈ 1.57 using the 2-week Klagenfurt campaign data, assuming C = 2.14 for quartz filter (Weingartner et al, 2003). There is some uncertainty with this value since values of C for quartz filter as obtained by comparisons with other techniques differ (Weingartner et al, 2003;Collaud Coen et al, 2010;Müller et al, 2011a, Segura et al, 2014.…”
Section: Influence Of the Filter Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the TFE-coated glass filter we obtained C ≈ 1.57 using the 2-week Klagenfurt campaign data, assuming C = 2.14 for quartz filter (Weingartner et al, 2003). There is some uncertainty with this value since values of C for quartz filter as obtained by comparisons with other techniques differ (Weingartner et al, 2003;Collaud Coen et al, 2010;Müller et al, 2011a, Segura et al, 2014.…”
Section: Influence Of the Filter Materialsmentioning
confidence: 99%
“…The enhancement parameter C has no statistically significant spectral dependence (Weingartner et al, 2003;Segura et al, 2014), with its value determined by comparing different methods and instruments in laboratories and in ambient observatories (Weingartner et al, 2003;Collaud Coen et al, 2010;Müller et al, 2011a;Segura et al, 2014), resulting in a range of values. The value of C may depend on the particle properties, as shown for the particle soot absorption photometer (PSAP) (Nakayama et al, 2010).…”
Section: Black Carbon Concentration Calculationmentioning
confidence: 99%
“…To estimate the particulate mass (PM 1 ) BC concentration a correction factor of 0.9 was used following Poulain et al (2014). The measurement accuracy of an individual MAAP yields a variability of less than 5 % around the mean value (Müller et al, 2011). Taking into account uncertainties of the mass absorption coefficient, the different particle cut size, and instrumentation accuracy, a total uncertainty of approximately 30 % is expected for the estimated BC mass concentrations.…”
Section: Multi-angle Absorption Photometer (Maap)mentioning
confidence: 99%
“…The MAAP monitors backscattering at 130 and 165 in addition to forward scattering and transmission at 0 , and inverts a parameterized radiative transfer model to obtain an absorption estimate yielding the observed pattern. The MAAP's internalized corrections have been found to reduce but not eliminate measurement biases Chow et al 2009;Collaud Coen et al 2010;Muller et al 2011;Hyvarinen et al 2013). MAAP measurements have recently been chosen as the reference values in multi-instrument comparisons lacking more fundamental methods such as photoacoustic analysis or paired extinction and scattering determinations (Collaud Coen et al 2010;Muller et al 2011).…”
mentioning
confidence: 99%
“…Hansen et al (1984) developed a continuous integrating plate monitor using optically thick quartz fiber filters, and instrument vendors have since produced a variety of user-ready monitors derived from this and other integrating plate designs. A great deal of work has been done to characterize and reconcile the responses of such instruments to realistic aerosols, both in the lab (Gerber and Hindman 1982;Clarke et al 1987;Hitzenberger 1993;Horvath 1993;Bond et al 1999;Weingartner et al 2003;Sheridan et al 2005;Muller et al 2011) and through comparisons in the field (Liousse et al 1993;Reid et al 1998;Schmid et al 2006;Chow et al 2009;Collaud Coen et al 2010). These studies have identified sources of measurement bias that can be loosely grouped into three categories requiring different forms of correction: filter effects, loading dependence, and particle scattering interference.…”
mentioning
confidence: 99%